COVID-19 Vaccination Services in the Region Kubu Raya District Border - Triyono, Joko; Apriyanto, Dhidik; Elyta, Elyta; Siringo, Tulus Gover; Lutfie, Ratu Zahira (International Journal of Multidisciplinary Approach Research and Science, 2023)
The high spread of COVID-19 in Indonesia has impacted various aspects of life, both social, cultural, and economic. To tackle the spread of COVID-19, the government has created a vaccination program to increase immunity against diseases due to COVID-19. The survey results by the Ministry of Health of the Republic of Indonesia show that even though it is free, people who volunteer to be vaccinated against COVID-19 still need to meet expectations. Nationally, it is only 65%, while West Kalimantan is only 63%. In Kubu Raya Regency, up to August 2021, positive cases of COVID-19 reached 3,336 points; 71.82% of people who had received vaccine I got 71.82% and vaccine II only 47.67%. Service quality is one of the factors that can determine the success of the vaccination program. This research aims to define community expectations regarding the quality of COVID-19 vaccination services by Community Health Centers in the border areas of Kubu Raya Regency. The research method is quantitative, and data analysis uses the average method and Cartesian diagrams. The research results show that the COVID-19 vaccination service in Kubu Raya Regency uses a pick-up and drop-off model, meaning that the service needs to be carried out at the Community Health Center. Still, officers go to the community with elementary requirements. The COVID-19 vaccination service is carried out at the Village Hall. Officer services still need to be entirely in line with community expectations. The public expects excellent service quality; the quality of COVID-19 vaccination services is still in the good category.